Malignant primary pulmonary meningioma with bone metastasis. Issue 2 (28th February 2020) - Minami, Yusuke; Sato, Shingo; Koyanagi, Hirotaka; Kinowaki, Yuko
Abstract: Primary pulmonary meningioma is extremely rare and only <45 cases have been reported since its first report by Kemnitz and Heinrich (Meningioma of lung: first report with light and electronmicroscopic findings. Ultrastruct. Pathol. 1982;3:359–65). Among these cases, only five cases were malignant or atypical. A 67-year-old female with primary pulmonary meningioma underwent thoracoscopic pulmonary wedge resection of the left lower lobe a year before. She had been aware of left thigh pain for 9 months, then she was referred to our division. Positron emission tomography-computed tomography suspected multiple bone metastasis including frontal bone, mandible, left scapula, rib, vertebra, pubis, left femur and sternum. We performed a needle biopsy of the sternum. Histopathological diagnosis was metastasis of primary pulmonary meningioma, World Health Organization grade III. We treated her with denosumab and radiation therapy targeting the left femur. Two months after the treatment, the pain had decreased and she could walk with no cane. No case of malignant extracranial meningioma with bone metastasis have been reported.